2020
DOI: 10.3389/fcell.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

Hec1/Ndc80 Tail Domain Function at the Kinetochore-Microtubule Interface

Abstract: Successful mitotic cell division is critically dependent on the formation of correct attachments between chromosomes and spindle microtubules. Microtubule attachments are mediated by kinetochores, which are large proteinaceous structures assembled on centromeric chromatin of mitotic chromosomes. These attachments must be sufficiently stable to transduce force; however, the strength of these attachments are also tightly regulated to ensure timely, error-free progression through mitosis. The highly conserved, ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 141 publications
(281 reference statements)
1
34
0
Order By: Relevance
“…We cannot exclude the possibility that PLK1 recruitment to BUB1 and CENP-U activates downstream phosphorylation events that promote hierarchical recruitment of PLK1 to additional receptors, thus explaining the plethora of different potential PLK1 kinetochore receptors previously identified (see Introduction ). Because our PLK1 localization experiments were performed in nocodazole, i.e., in the absence of microtubules, they do not exclude recruitment of PLK1 to additional receptors generated after recruitment of “late” kinetochore residents, such as the SKA and SKAP complexes ( Wimbish and DeLuca, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that PLK1 recruitment to BUB1 and CENP-U activates downstream phosphorylation events that promote hierarchical recruitment of PLK1 to additional receptors, thus explaining the plethora of different potential PLK1 kinetochore receptors previously identified (see Introduction ). Because our PLK1 localization experiments were performed in nocodazole, i.e., in the absence of microtubules, they do not exclude recruitment of PLK1 to additional receptors generated after recruitment of “late” kinetochore residents, such as the SKA and SKAP complexes ( Wimbish and DeLuca, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2017 ). The Hec1 protein contains an N-terminal, unstructured “tail” domain that has also been implicated in forming kinetochore–microtubule attachments in cells, although the requirement for the tail domain in this process varies among eukaryotic species ( Wimbish and DeLuca, 2020 ). The Hec1 tail domain in Saccharomyces cerevisiae and Caenorhabditis elegans is dispensable for formation of stable kinetochore–microtubule attachments ( Kemmler et al.…”
Section: Introductionmentioning
confidence: 99%
“…The positive and negative correlated genes were represented. Furthermore, the results of cellular component module of GO Ontology suggested that APEX2 was closely associated with the kinetochore and spindle microtubule (Figure 4B ), two main cellular components involved in cell proliferation[ 23 ]. The significant enrichment score suggested that APEX2 may be involved in the positive regulation of liver cancer cell proliferation.…”
Section: Resultsmentioning
confidence: 99%